EFFECT OF ATHERMAL MILLIMETER ELECTROMAGNETIC RADIATION ON DNA STRUCTURE OF TUMOR TISSUE $IN~VIVO$ - Tadevosyan, A.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
$In~vivo$ effect of non thermal millimeter electromagnetic waves (MEMWs) with $50.3~GHz$ (which coincides with resonant frequencies of oscillations of water molecular structures) and $48.3~GHz$ (which does not coincide with resonant frequencies) frequencies on DNA primary and secondary structures of liver of healthy rats as well as Sarcoma-45 tumor carrying rats has been studied. It was shown, that under the effect of MEMWs with $50.3~GHz$ during $60~min$, the content of 5-methylcitosine, the melting parameters of DNA of Sarcoma-45 tumors changed and approached to respective values of DNA extracted from the liver of healthy animals.
Keywords: DNA, millimeter electromagnetic waves, Sarcoma-45.